Comparative genomic analyses of Mycoplasma synoviae vaccine strain MS-H and its wild-type parent strain 86079/7NS: implications for the identification of virulence factors and applications in diagnosis of M. synoviae. Issue 6 (2nd November 2019) - Zhu, Ling; Shahid, Muhammad A.; Markham, John; Browning, Glenn F.; Noormohammadi, Amir H.; Marenda, Marc S.
ABSTRACT: Mycoplasma synoviae is an economically important avian pathogen worldwide, causing respiratory disease, infectious synovitis, airsacculitis and eggshell apex abnormalities in commercial chickens. Despite the widespread use of MS-H as a live attenuated vaccine over the past two decades, the precise molecular basis for loss of virulence in this vaccine is not yet fully understood. To address this, the whole genome sequence of the vaccine parent strain, 86079/7NS, was obtained and compared to that of the MS-H vaccine. Except for the vlhA expressed region, both genomes were nearly identical. Thirty-two single nucleotide polymorphisms (SNPs) were identified in MS-H, including 11 non-synonymous mutations that were predicted, by bioinformatics analysis, to have changed the secondary structure of the deduced proteins. One of these mutations caused truncation of the oppF-1 gene, which encodes the ATP-binding protein of an oligopeptide permease transporter. Overall, the attenuation of MS-H strain may be caused by the cumulative and complex effects of several mutations. The SNPs identified in MS-H were further analyzed by comparing the MS-H and 86079/7NS sequences with the strains WVU-1853 and MS53. In the genomic regions conserved between all strains, 30 SNPs were found to be unique to MS-H lineage. These results have provided a foundation for developing novel biomarkers for the detection of virulence in M. synoviae and also for designing new genotyping assays for discrimination of MS-H from field strains.